Biodiversity of molluscs in the Multiple-Use Natural Reserve Guillermo Enrique Hudson in Florencio Varela, Buenos Aires, Argentina - Díaz, Ana Carolina (2013)
The present study provides a list of freshwater molluscs species from the Davidson Stream in the Multiple Use Natural Reserve Guillermo Enrique Hudson, Florencio Varela, Buenos Aires, Argentina. In the survey performed in the months of March, April, and September 2009, 505 specimens were captured. Analysis of the taxocenosis of the molluscs of the stream revealed the presence of nine taxa belonging to 8 different families with five of the species being Gastropoda and four Bivalvia.